Grip force measurement of soft- Actuated finger exoskeleton - Nordin, I. N. A. M. (Penerbit UTM Press, 2016)
Over recent years, the reseach in the field of soft actuation has been extensively increased for achieving more complex motion path with smooth, high flexible movement and high generated force at minimum operating pressure. This paper presents the study on gripping force capability of soft actuators applied on glove-type finger exoskeleton, developed in motivation to assist individuals having weak finger gripping ability in their rehabilitation exercise towards hand function restoration. The exoskeleton utilizes five cylindrical shaped pneumatic bending actuators developed in the lab, which use fiber reinforcement as a cause of bending motion that drive finger’s flexion movement. Four right-handed healthy volunteers simulated paralysis participated in the study. At 200kPa safe operating pressure, the soft exoskeleton worn by the subjects demonstrates the ability to provide adequate grip force. The grip force generated from exoskeleton worn on passive right hand is 4.66 ± 0.2 N and 3.61± 0.2 N from passive left hand, both higher than the minimum grip forces measured to hold the Hand Dynamometer of 240 g. It shows good potential to be used as a finger rehabilitation assist device.